X inactivation as a mechanism of selection against lethal alleles: further investigation of incontinentia pigmenti and X linked lymphoproliferative disease. Issue 9 (September 1992) - Harris, A; Collins, J; Vetrie, D; Cole, C; Bobrow, M
Abstract : Thirty-one females with incontinentia pigmenti (IP), 42 controls, and 11 females from four families segregating for X linked lymphoproliferative disease (XLP) were studied for evidence of skewed X inactivation by analysis of methylation at sites in the HPRT, PGK, and M27 beta (DXS255) regions of the X chromosome. Extensive skewing of X inactivation was present in blood from 4/42 (9.5%) control females and 11/31 (35%) of those with IP. This frequency of skewed inactivation was seen in both familial and sporadic cases of IP. Analysis of inactivation in mother/daughter pairs, both affected and control subjects, showed no familial consistency of pattern, arguing against specific mutations being associated with particular patterns of inactivation. In the only informative family where both mother and daughter were affected by IP and showed skewed inactivation, the IP mutation was on the active X chromosome. This argues against cell selection during early embryogenesis being the explanation for the skewed inactivation observed. These data confirm that skewed inactivation of one X is observed in lymphocytes from a significant minority of normal females, and is seen with raised frequency in IP heterozygotes. It is not, however, a universally observed phenomenon, and the relationship of X inactivity to the IP mutation appears to be complex. In the case of XLP, though skewed X inactivation patterns are seen in most disease carriers, the frequency with which this phenomenon occurs in normal females renders it an unreliable diagnostic marker for XLP carriers.